Exfoliative cytology as a tool in the preinvasive anal lesions diagnosis - Javier Martínez Navarro (Medisur, 2024)
The anal cancer increase in high-risk populations stimulates the implementation of protocols to carry out early diagnosis, as well as the monitoring of high-grade anal intraepithelial neoplasia as a precursor lesion. From the cytological point of view, these lesions can be defined in a similar way to lesions of the uterine cervix, and therefore, the Bethesda classification can be used, which differentiates several categories: normal epithelium, low-grade squamous intraepithelial lesion, squamous intraepithelial lesion high grade, atypical squamous cells of undetermined significance and atypical squamous cells not exclusive of high grade lesion. This cytological differentiation between low-grade and high-grade squamous intraepithelial lesions has a histological correspondence when analyzing the biopsy performed in the anal canal, which is the fundamental tool for the diagnosis of anal intraepithelial neoplasia. In this context, reference is made to anal cytology as a very useful resource for screening anal intraepithelial lesions.